Dampak Konvergensi IFRS, Karakteristik Perusahaan, dan Kualitas Auditor Terhadap Audit Delay - Ratmono, Dwi; Septiana, Puspa Avinda Dwi (Universitas Muhammadiyah Yogyakarta, Indonesia, 2015)
The objective of this study is to examine the influence of IFRS implementation on the audit delay. To focus on the impact of audit delay, this study controls the effect of company’s characteristics. Characteristics of the company used in this study are the company size, the leverage, and the loss announcement. The population used in this study is all of the manufacturing company listed in Indonesia Stock Exchange for 2010 until 2013 period. The study uses the purposive sampling for the sampling method. The criteria of the sample which is used is company must have published audited financial report for four years successively and used Rupiah, so that the number of the sample in this study is 416 observations. There are two variables that do not affect the audit delay, those IFRS implementation, and loss announcement..The results shows that the company size, leverage and the auditor’s quality significantly affect audit delay.